2021
DOI: 10.32098/mltj.01.2021.20
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Longus Colli Muscle in Women with and without Forward Head Posture

Abstract: Background. Forward head posture (FHP) is the most common poor postures in patients with shoulder and neck pain. Longus colli (LCo) muscle has important role in maintaining normal posture of the cervical spine and dysfunction of this muscle may lead to abnormal posture of the cervical spine. Ultrasonography is one of the most common methods used to evaluate muscle performance. The aim of this study was to compare performance of LCo muscle between women with and without FHP. Methods. This cross-sectional study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The results of a previous study showed greater muscle thickness change of LCo during craniocervical flexion in subjects without FHP compared subjects with FHP [19]. This can be explained by the fact that the FHP translated forward in relation to a vertical reference line [2,22,27], as well as the disuse of the DCF muscles in daily living and overuse of the SCM muscle in neck flexion movements [19]. For SCM, there was no significant difference in the SCM muscle thickness and muscle thickness changing ratio between subjects with and without FHP.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…The results of a previous study showed greater muscle thickness change of LCo during craniocervical flexion in subjects without FHP compared subjects with FHP [19]. This can be explained by the fact that the FHP translated forward in relation to a vertical reference line [2,22,27], as well as the disuse of the DCF muscles in daily living and overuse of the SCM muscle in neck flexion movements [19]. For SCM, there was no significant difference in the SCM muscle thickness and muscle thickness changing ratio between subjects with and without FHP.…”
Section: Discussionmentioning
confidence: 82%
“…In a previous study, the DCF thickness was shown to be reduced in subjects with FHP compared to those without FHP [27]. In a previous study, the muscle thickness of the LCo in the resting state, contraction state (50% of maximal isometric contraction of craniocervical flexion), and thickness change between subjects with and without FHP were measured using ultrasonography [19]. Participants performed craniocervical flexion movements while push on the inferior load cell placed on their chin in a sitting position [19].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations